2022
DOI: 10.1002/cncr.34061
|View full text |Cite
|
Sign up to set email alerts
|

Delivering colorectal cancer screening integrated with primary health care services in Morocco: Lessons learned from a demonstration project

Abstract: BACKGROUND: Colorectal cancer (CRC) incidence and mortality rates are increasing rapidly in many low-income and middle-income countries. A demonstration project was implemented in Morocco in collaboration with the Ministry of Health to assess the feasibility, acceptability, and challenges of implementing CRC screening through routine primary care facilities. METHODS: The objective of the project was to screen 10,000 men and women aged 50 to 75 years through 10 primary health centers (PHCs) in 2 provinces. All … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 25 publications
(31 reference statements)
0
14
0
1
Order By: Relevance
“…Indirect approaches, which emphasize external systems or policies that influence surgical cancer care, have also been a source of interest to researchers. For example, a study in Morocco sought to improve early cancer detection rates by providing point‐of‐care fecal immunochemical testing at primary health centers and offering colonoscopies for those who tested positive 56 ; however, only 62.6% of those who tested positive successfully underwent a subsequent colonoscopy, with many patients citing logistical and financial barriers to attending the follow‐up procedure and appointments. Furthermore, the increased burden on the Moroccan surgical infrastructure due to more patients seeking colonoscopies secondary to the positive fecal screening intervention resulted in increased wait times and, as a result, decreased compliance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indirect approaches, which emphasize external systems or policies that influence surgical cancer care, have also been a source of interest to researchers. For example, a study in Morocco sought to improve early cancer detection rates by providing point‐of‐care fecal immunochemical testing at primary health centers and offering colonoscopies for those who tested positive 56 ; however, only 62.6% of those who tested positive successfully underwent a subsequent colonoscopy, with many patients citing logistical and financial barriers to attending the follow‐up procedure and appointments. Furthermore, the increased burden on the Moroccan surgical infrastructure due to more patients seeking colonoscopies secondary to the positive fecal screening intervention resulted in increased wait times and, as a result, decreased compliance.…”
Section: Resultsmentioning
confidence: 99%
“…7,16,43 Broader health system gaps Indirect approaches, which emphasize external systems or policies that influence surgical cancer care, have also been a source of interest to researchers. For example, a study in Morocco sought to improve early cancer detection rates by providing point-of-care fecal immunochemical testing at primary health centers and offering colonoscopies for those who tested positive 56 ; however, only 62.6% of those who tested positive successfully underwent a subsequent colonoscopy, with many patients citing logistical and financial barriers to attending the follow-up procedure and appointments.…”
Section: Limited Resources and Perioperative Servicesmentioning
confidence: 99%
“…Alatise et al [ 22 ] reported that high numbers of false-positive results from FITs generated a large endoscopic burden for a country with a paucity of endoscopic resources. Similarly, Selmouni et al [ 27 ] reported that increased colonoscopy referral led to increased waiting times and thus reduced adherence to follow-up CRC screening by those with an initial positive test result.…”
Section: Resultsmentioning
confidence: 99%
“…Another barrier to CRC screening in Africa was the lack of patient knowledge [ 13 , 17 , 18 , 20 , 26 , 27 ]. Lussiez et al [ 13 ] reported that 86.2% of physicians interviewed in Ghana identified patients’ lack of awareness of screening, specifically patients not perceiving CRC as a serious health threat, as a barrier to CRC screening.…”
Section: Resultsmentioning
confidence: 99%
“…In their article in this issue, Selmouni and colleagues report on the feasibility, acceptability, and implementation challenges of delivering an opportunistic colorectal cancer screening program that offers fecal immunochemical testing (FIT) as part of routine primary care in Morocco. 1 The study consented and enrolled nearly 10,000 patients from 10 primary care clinics in 2 Moroccan provinces. Of the 9908 individuals aged 50 to 75 years who completed an FIT, 73.3% were women, 460 (4.7%) had an abnormal test result, and 288 (62.6% of those with an abnormal test) completed a follow-up colonoscopy.…”
mentioning
confidence: 99%